2011
DOI: 10.2495/sdp-v6-n4-420-446
|View full text |Cite
|
Sign up to set email alerts
|

Planned gentrification in istanbul: the sulukule renewal area 2005-2010

Abstract: This paper evaluates the fi rst local government-led neighborhood regeneration project in central Istanbul with reference to its neighborhood impact and its wider implications for the future of regeneration in the city. From a perspective rooted in historical and international comparative planning studies, the research methodology is elaborated through an analysis of the evolution of a generic model of contemporary sustainable urban regeneration that provides the analytical framework for the evaluation. A revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Residents under threat of expropriation were effectively forced to sell and move out of their neighbourhood and tenants were the victims of forced eviction from their homes. This was the authoritarian and coercive process at the heart of the controversial redevelopment of Sulukule, characterised as "planned gentrification" (Kocabas and Gibson 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Residents under threat of expropriation were effectively forced to sell and move out of their neighbourhood and tenants were the victims of forced eviction from their homes. This was the authoritarian and coercive process at the heart of the controversial redevelopment of Sulukule, characterised as "planned gentrification" (Kocabas and Gibson 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Between 1999 and 2012, an increasing number of neighbourhood regeneration projects were developed and implemented using the evolving framework. However, most were highly controversial as they resulted in the displacement and dispersal of the residents in a process which came to be characterised as "planned gentrification" (Kocabas and Gibson 2011). The United Nations Advisory Group on Forced Evictions which visited Istanbul's 8 regeneration areas in 2009 reported that approximately 80,000 people were directly affected and 12,730 people had already had their homes destroyedsee Figure 2 (AGFE 2009).…”
Section: Early Experience Of the Implementation Of Neighbourhood Redementioning
confidence: 99%
See 2 more Smart Citations
“…But the comprehensive redevelopment of the area was the antithesis of sustainable urban conservation. Virtually all the neighbourhood's housing and infrastructure, its environmental capital, was destroyed, as well as its intangible cultural heritagethe 1000 years old Romany community [21]. The ongoing implementation of Renewal Areas programme does not involve comprehensive redevelopment, but a combination of redevelopment and rehabilitation.…”
Section: A Green Historic Peninsula?mentioning
confidence: 99%